2014
DOI: 10.1371/journal.pone.0087810
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Metabolite Compound K Promotes Recovery of Dextran Sulfate Sodium-Induced Colitis and Inhibits Inflammatory Responses by Suppressing NF-κB Activation

Abstract: Phytogenic compounds with anti-oxidant and anti-inflammatory properties, such as ginsenoside metabolite compound K (CK) or berberine (BBR), are currently discussed as promising complementary agents in the prevention and treatment of cancer and inflammation. The latest study showed that ginsenoside Rb1 and its metabolites could inhibit TNBS-induced colitis injury. However, the functional mechanisms of anti-inflammation effects of ginsenoside, particularly its metabolite CK are still not clear. Here, using dextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 38 publications
5
80
0
Order By: Relevance
“…Inflammatory cytokine release and neutrophil infiltration play important roles in the process of inflammation [17][18][19] . The present study indicated that levels of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) and myeloperoxidase (MPO) activity in the resected colon from TNBS-treated rats were significantly higher than in the vehicle control ( Figure 3A).…”
Section: Geniposide-induced Amelioration On Intestinal Inflammation Imentioning
confidence: 99%
“…Inflammatory cytokine release and neutrophil infiltration play important roles in the process of inflammation [17][18][19] . The present study indicated that levels of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) and myeloperoxidase (MPO) activity in the resected colon from TNBS-treated rats were significantly higher than in the vehicle control ( Figure 3A).…”
Section: Geniposide-induced Amelioration On Intestinal Inflammation Imentioning
confidence: 99%
“…Although the anti-inflammatory effects of ginsenosides and its remedy effects against IBD have been well reported, the molecular mechanisms remain established (Yang et al, 2012a;Li et al, 2014;Ye et al, 2014). Here we hypothesized that ginsenosides may elicit its anti-inflammatory effects in IBD via restoring PXR/NF-kB signaling in the inflamed colon.…”
Section: Introductionmentioning
confidence: 91%
“…Ginsenosides are responsible for the majority of functions of ginseng, including angiogenesis, vasorelaxation and antioxidation (8). These molecules also possess anti-inflammatory and anticancer properties (12)(13)(14). In a previous study, four dammarane-type triterpene saponins isolated from the Panax ginseng root exhibited effective hydroxyl radical scavenging ability, as well as antibacterial and cytotoxic activities (15).…”
Section: Kip1mentioning
confidence: 97%